Nocturnal warming accelerates drought-induced seedling mortality of two evergreen tree species. (17th December 2021) - Lu, Ruiling; Du, Ying; Sun, Huanfa; Xu, Xiaoni; Yan, Liming; Xia, Jianyang
Abstract: Extreme drought is one of the key climatic drivers of tree mortality on a global scale. However, it remains unclear whether the drought-induced tree mortality will increase under nocturnal climate warming. Here we exposed seedlings of two wide-ranging subtropical tree species, Castanopsis sclerophylla and Schima superba, with contrasting stomatal regulation strategies to prolonged drought under ambient and elevated night-time temperature by 2 °C. We quantified the seedling survival time since drought treatment by measuring multiple leaf traits such as leaf gas exchange, predawn leaf water potential and water-use efficiency. The results showed that all seedlings in the ambient temperature died within 180 days and 167 days of drought for C. sclerophylla and S. superba, respectively. Night warming significantly shortened the survival time of C. sclerophylla, by 31 days, and S. superba by 28 days, under the drought treatment. A survival analysis further showed that seedlings under night warming suffered a 1.6 times greater mortality risk than those under ambient temperature. Further analyses revealed that night warming suppressed net leaf carbon gain in both species by increasing the nocturnal respiratory rate of S. superba across the first 120 days of drought and decreasing the photosynthetic rate of both species generally after 46 days of drought. These effects on net carbon gain were more pronounced in S. superba than C. sclerophylla . After 60 days of drought, night warming decreased the predawn leaf water potential and leaf water-use efficiency of C. sclerophylla but not S. superba . These contrasting responses are partially due to variations in stomatal control between the two species. These findings suggest that stomatal traits can regulate the response of leaf gas exchange and plant water-use to nocturnal warming during drought. This study indicates that nocturnal warming can accelerate tree mortality during drought. Night warming accelerates the mortality of two subtropical seedlings under drought. Night warming differently affects the drought response of leaf gas exchange and plant water-use between the two species due to species-specific stomatal morphological traits. Carbon metabolism changes and hydraulic damage play differential roles in driving night-warming impacts on the drought-induced mortality between the two species.